Effects of different exposed crystal surfaces of CeO2 loaded on an MnO2/X catalyst for the NH3-SCR reaction. Issue 27 (28th June 2022) - Wang, Shihao; Li, Xiaodi; Ren, Shan; Xing, Xiangdong; Chen, Lin; Yang, Jie; Liu, Manyi; Xie, Yixin
Abstract : To study the effects of the loading of different exposed crystal surfaces of CeO2 on an MnO2 /X catalyst for the NH3 -selective catalytic reduction (SCR) reaction, Mn/X, Mn–CeNP /X, Mn–CeNC /X and Mn–CeNR /X catalysts were synthesized via a solid-state diffusion method. Abstract : To study the effects of the loading of different exposed crystal surfaces of CeO2 on an MnO2 /X catalyst for the NH3 -selective catalytic reduction (SCR) reaction, Mn/X, Mn–CeNP /X, Mn–CeNC /X and Mn–CeNR /X catalysts were synthesized via a solid-state diffusion method. Scanning electron microscopy (SEM), X-ray diffractometry (XRD), Brunauer–Emmett–Teller (BET) analysis, X-ray photoelectron spectroscopy (XPS), hydrogen temperature-programmed reduction (H2 -TPR), ammonia temperature-programmed desorption (NH3 -TPD) and in situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) measurements were used to characterize the physicochemical properties and reaction mechanism of the prepared catalysts. The results exhibted that the Mn–CeNC /X catalyst showed superior low-temperature activity in the range of 100–200 °C, and the Mn–CeNR /X catalyst showed better N2 selectivity and SO2 resistance in the NH3 -SCR reaction. This indicated that the loading of different exposed crystal surfaces of CeO2 could have a huge impact on the SCR performance of Mn/X catalysts. According to the characterization results, the surperior low-temperature SCR activity of the Mn–CeNC /X catalyst could be attributed to its abundant acidic sites, excellent reducibility, high Mn 4+ /(Mn 2+ + Mn 3+ + Mn 4+ ) ratio and abundant surface chemisorbed labile oxygen. However, the Mn–CeNR /X catalyst exhibited better N2 selectivity in the NH3 -SCR reaction, which could be attributed to the low ratio of Mn 4+ /(Mn 4+ + Mn 3+ + Mn 2+ ) and its strong adsorption capacity toward NO. Finally, possible reaction pathways and a mechanism model of the Mn–CeNC /X catalysts were proposed.